CORTICAL INVOLVEMENT IN THE STARTREACT EFFECT - Stevenson, Andrew J. T. (2014)
The rapid release of prepared movements by a loud acoustic stimulus capable of eliciting a startle response has been termed the StartReact effect (Valls-Solé et al., 1999), and premotor reaction times (PMTs) of <70 ms are often observed. Two explanations have been given for these short latency responses. The subcortical storage and triggering hypothesis suggests movements that can be prepared in advance of a “go” signal are stored and triggered from subcortical areas by a startling acoustic stimulus (SAS) without cortical involvement. Alternatively, it has been hypothesized that the SAS can trigger movements from cortical areas through a faster pathway ascending from subcortical structures. Two experiments were designed to examine the possible role of primary motor cortex in the StartReact effect. In Experiment 1, we used suprathreshold transcranial magnetic stimulation (TMS) during the reaction time (RT) interval to induce a cortical silent period in the contralateral primary motor cortex (M1). Thirteen participants performed 20° wrist extension movements as fast as possible in response to either a control stimulus (82dB) or SAS (124 dB). PMTs for startle trials were faster than control trials, while TMS significantly delayed movement onset compared to No TMS or Sham TMS conditions. In Experiment 2, we examined the StartReact effect in a highly cortically represented action involving speech of a consonant-vowel (CV) syllable. Similar to previous work examining limb movements, a robust StartReact effect was found. Collectively, these experiments provide evidence for cortical (M1) involvement in the StartReact effect.